2022
DOI: 10.1038/s41598-022-11069-z
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization for simultaneous removal of methyl red and production of fatty acid methyl esters using fresh alga Scenedesmus obliquus

Abstract: Microalgae are a diverse group of microorganisms, the majority of which are photosynthetic in nature. Microalgae have different applications, the most important of which is the biological treatment of wastewater. Microalgae grow in various types of wastewater, such as wastewater polluted by Azo dyes, due to microalgae using wastewater as a culture medium, which contains many nutrients like nitrogen, phosphate, and carbon sources. Microalgae grow in various types of wastewater, such as wastewater polluted by Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Shen et al 91 reported that mixotrophic conditions with nitrogen www.nature.com/scientificreports/ depletion led to high FAME produced by S. obliquus. El-Naggar et al 92 reported that S. obliquus proved efficiency in eliminating dyes and produce renewable fuels, such as biodiesel (Table 2).…”
Section: Infrared Measurements (Ir)mentioning
confidence: 99%
“…Shen et al 91 reported that mixotrophic conditions with nitrogen www.nature.com/scientificreports/ depletion led to high FAME produced by S. obliquus. El-Naggar et al 92 reported that S. obliquus proved efficiency in eliminating dyes and produce renewable fuels, such as biodiesel (Table 2).…”
Section: Infrared Measurements (Ir)mentioning
confidence: 99%